Innovation in Neighborhood Management Web Service: A Precise Initiative to Augment Audiences' Interaction on Social Media - Sadiq, Muhammad Waqas; Huo, Chunhui; Almogren, Abeer S.; Aljammaz, Norah Abdullah; Al-Rahmi, Waleed Mugahed; Al-maatuok, Qusay; Zulfiqar, Salman (Frontiers in Psychology, 2022)
For this article, two significant elements in social media websites, system operation and social technology will be examined in connection to website visitors' online loyalty and interaction, namely Commitment and satisfaction, in neighbourhood management through social media websites. Two hundred fifty-one social media users completed a systematic questionnaire. After confirmatory factor analysis, data were examined in AMOS 24 using structural equation modelling with bootstrap. The research showed that both variables indirectly influence website visitors' online loyalty and interaction via trust and satisfaction, but not directly. Online relationship quality characteristics impact the interaction pattern of social media users after changes in services applied by the respective organisations on their websites. As for managers, the research gives crucial data on user behaviour in connection to new services launched by organisations on their websites and shows how value creation to the target audience may help them reduce costs and optimise revenues.